Manganese ferrite / bismuth tungstate heterojunction photocatalyst as well as preparation method and application thereof
By constructing a heterojunction photocatalyst for manganese ferrite/bismuth tungstate, the problem of low separation efficiency of photogenerated electrons and hole pairs is solved, and more efficient photocatalytic carbon dioxide reduction is achieved, with good photocatalytic performance and large-scale production potential.
Patent Information
- Application Number
- CN202510560249.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2045-04-30
AI Technical Summary
Existing single-component photocatalysts are difficult to effectively separate photogenerated electrons and hole pairs, resulting in low photocatalytic carbon dioxide reduction efficiency.
By constructing a heterojunction photocatalyst for manganese ferrite/bismuth tungstate, the heterojunction structure of manganese ferrite and bismuth tungstate was prepared by alkali etching method, which improved the separation efficiency of carriers, and prepared bismuth tungstate and manganese ferrite nanoflower structures by hydrothermal method to provide more reactive sites.
The photocatalytic reduction of carbon dioxide activity of the photocatalytic catalyst is improved, and the photocatalytic reduction capability is stronger. The preparation method is simple and low-cost, and it is suitable for large-scale production.
Smart Images

Figure CN120420995A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalytic materials, and in particular relates to a manganese ferrite / bismuth tungstate heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] Photocatalytic carbon dioxide reduction uses inexhaustible solar energy as energy, and can directly convert carbon dioxide gas into hydrocarbon solar fuels. It is a feasible method to solve both the energy crisis and environmental pollution. Therefore, bismuth tungstate (Bi2WO6) is a narrow bandgap semiconductor and a typical Aurivillius phase oxide, which has been widely studied in the field of photocatalysis. It is composed of [Bi2O2] 2+ layer and [WO4] 2- The photocatalyst is composed of alternating layers, with oxygen atoms shared between the layers. This staggered stacked structure helps promote the separation of photogenerated carriers. However, under current circumstances, single-component photocatalysts have difficulty effectively separating photogenerated electron and hole pairs.
[0003] Manganese ferrite, due to its narrow band gap, excellent photochemical stability, and environmental friendliness, has broad photocatalytic applications and can be combined with Bi2WO6 to create heterostructures. Manganese ferrite, also a transition metal oxide, can enhance the adsorption of carbon dioxide by Bi2WO6 by introducing active metal sites. The construction of a manganese ferrite / bismuth tungstate heterojunction improves carrier separation efficiency, thereby enhancing the photocatalytic activity of Bi2WO6. Summary of the Invention
[0004] In response to the deficiencies in the prior art, the present invention provides a method for preparing a manganese ferrite / bismuth tungstate photocatalyst and its application in the photocatalytic reduction of carbon dioxide. The method is simple, convenient, low-cost, requires mild conditions, and is conducive to large-scale production. The obtained manganese ferrite / bismuth tungstate photocatalyst has good photocatalytic reduction activity for carbon dioxide.
[0005] The technical solution adopted in the present invention is:
[0006] A manganese ferrite / bismuth tungstate heterojunction photocatalyst, wherein the molar ratio of the manganese ferrite to the total molar mass of the heterojunction photocatalyst is 1:10, 2:10, 3:10 or 5:10.
[0007] The above-mentioned method for preparing a manganese ferrite / bismuth tungstate heterojunction photocatalyst comprises the following steps:
[0008] 1) Dissolve sodium tungstate dihydrate, bismuth nitrate pentahydrate and hexadecyltrimethylammonium bromide in deionized water and perform hydrothermal reaction to obtain bismuth tungstate;
[0009] 2) dissolving ferric chloride hexahydrate and manganese chloride tetrahydrate in water, adding sodium hydroxide solution, and subjecting to a hydrothermal reaction to obtain manganese ferrite;
[0010] 3) dissolving bismuth tungstate and manganese ferrite in a sodium hydroxide solution, stirring, and drying to obtain a manganese ferrite / bismuth tungstate heterojunction photocatalyst.
[0011] Furthermore, in the above preparation method, in step 1), sodium tungstate dihydrate: bismuth nitrate pentahydrate = 0.1-1 g: 0.5-1.5 g.
[0012] Furthermore, in the above preparation method, in step 1), the amount of cetyltrimethylammonium bromide added is 0.05-1 g.
[0013] Furthermore, in the above preparation method, in step 1), the temperature of the hydrothermal reaction is 80-150° C., and the time of the hydrothermal reaction is 18-36 hours.
[0014] Furthermore, in the above preparation method, in step 2), ferric chloride hexahydrate: manganese chloride tetrahydrate: sodium hydroxide = 1-4 g: 0.5-1.5 g: 0.0008-0.001 mol.
[0015] Furthermore, in the above preparation method, in step 2), the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 6-18 h.
[0016] Furthermore, in the above preparation method, in step 3), the stirring time is 1-5 hours.
[0017] Application of the above-mentioned manganese ferrite / bismuth tungstate heterojunction photocatalyst in photocatalytic reduction of carbon dioxide.
[0018] Furthermore, the above application method is as follows: under visible light irradiation, the manganese ferrite / bismuth tungstate heterojunction photocatalyst is placed in a closed space filled with carbon dioxide gas to reduce the carbon dioxide gas to carbon monoxide gas.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention uses an alkaline etching method to prepare a manganese ferrite / bismuth tungstate heterojunction photocatalyst. The heterojunction structure of this material can improve the carrier separation efficiency, thereby achieving the purpose of improving the photocatalytic activity.
[0021] 2. The present invention utilizes an alkaline etching method to construct a manganese ferrite / bismuth tungstate heterojunction photocatalyst. The bismuth tungstate nanoflowers have a large specific surface area and can provide more reactive sites in the photocatalytic reaction. The introduction of manganese ferrite can construct a heterostructure with bismuth tungstate, which is beneficial to further improve the carrier separation efficiency.
[0022] 3. The manganese ferrite / bismuth tungstate heterojunction photocatalyst prepared by the present invention has stronger photocatalytic reduction ability, participates in the catalytic reaction, and has good photocatalytic reduction performance of carbon dioxide. In addition, the method is simple, convenient, low-cost, mild in conditions, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 These are the XRD patterns of O-BWO, MFO, 10MFO / O-BWO, 20MFO / O-BWO, 30MFO / O-BWO and 50MFO / O-BWO.
[0024] Figure 2 This is the SEM image of MFO.
[0025] Figure 3 This is the SEM image of O-BWO.
[0026] Figure 4 This is the SEM image of 20MFO / O-BWO.
[0027] Figure 5 This is a comparison chart of the photocatalytic reduction of carbon dioxide reactions of O-BWO, MFO, 10MFO / O-BWO, 20MFO / O-BWO, 30MFO / O-BWO and 50MFO / O-BWO.
[0028] Figure 6 This is a comparison chart of the photocatalytic reduction of carbon dioxide activities of O-BWO, MFO, 10MFO / O-BWO, 20MFO / O-BWO, 30MFO / O-BWO and 50MFO / O-BWO. DETAILED DESCRIPTION
[0029] Example 1 A manganese ferrite / bismuth tungstate photocatalyst (the molar ratio of manganese ferrite to the total molar mass of the composite material is 1:10)
[0030] 1) Dissolve 0.33 g of sodium tungstate dihydrate, 0.97 g of bismuth nitrate pentahydrate, and 0.05 g of hexadecyltrimethylammonium bromide in 80 mL of deionized water. The resulting solution was stirred at room temperature for 2 hours, then transferred to a 100 mL stainless steel autoclave and heated at 120°C for 24 hours. The naturally cooled precipitate was collected by centrifugation and washed several times with deionized water and anhydrous ethanol. A white product was obtained after vacuum drying at 80°C for 12 hours. Finally, 0.1 g of bismuth tungstate was dispersed in 50 mL (1 mg / mL) of NaOH solution, stirred for 1 hour, and washed and dried to obtain oxygen vacancy bismuth tungstate (denoted as O-BWO).
[0031] 2) Dissolve 2.7029 g of ferric chloride hexahydrate and 0.9892 g of manganese chloride tetrahydrate in deionized water and stir for 30 minutes. Then, while stirring for 1 hour, add 10 mL of 0.08 mol / L sodium hydroxide solution dropwise. Place the solution in a 100 mL stainless steel autoclave and heat at 180°C for 10 hours. Finally, cool the solution to room temperature, filter, wash, and dry in an oven at 60°C for 12 hours to obtain manganese ferrite (MFO).
[0032] 3) 0.1 g of bismuth tungstate and 0.0036 g of manganese ferrite were mixed and dispersed in 50 mL (1 mg / mL) NaOH solution and stirred for 2 h. The mixture was washed and dried to obtain a manganese ferrite / oxygen vacancy bismuth tungstate composite material (denoted as 10MFO / O-BWO).
[0033] The O-BWO, MFO and 10MFO / O-BWO prepared in step 1), step 2) and step 3) were subjected to XRD test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the typical characteristic peaks of O-BWO and MFO were detected in 10MFO / O-BWO, indicating the successful preparation of 10MFO / O-BWO.
[0034] Example 2 Photocatalytic Reduction of Carbon Dioxide Using 10MFO / O-BWO Photocatalyst
[0035] The 10MFO / O-BWO photocatalyst prepared in Example 1 was used to perform a photocatalytic reduction of carbon dioxide experiment. The test process was as follows: using a 300W xenon lamp as the light source, 0.03g of O-BWO, MFO, and 10MFO / O-BWO prepared above were placed in a laboratory-made sealed reaction vessel with 1mL of deionized water. The sealed vessel was evacuated with a vacuum pump and carbon dioxide gas was passed through for three cycles, and then carbon dioxide was reduced under visible light irradiation. Figure 5 、 6 As shown in the figure, it can be seen that the manganese ferrite / bismuth tungstate photocatalyst prepared in Example 1 exhibits good photocatalytic activity and stability, and the carbon monoxide generation rate of 10MFO / O-BWO reaches 17.1 μmol h -1 g -1 , while the carbon monoxide generation rate of O-BWO was only 8.8 μmol h -1 g -1 .
[0036] Example 3 A manganese ferrite / bismuth tungstate photocatalyst (the molar ratio of manganese ferrite to the total molar mass of the composite material is 2:10)
[0037] 1) Dissolve 0.33 g of sodium tungstate dihydrate, 0.97 g of bismuth nitrate pentahydrate, and 0.05 g of hexadecyltrimethylammonium bromide in 80 mL of deionized water. The resulting solution was stirred at room temperature for 2 hours, then transferred to a 100 mL stainless steel autoclave and heated at 120°C for 24 hours. The naturally cooled precipitate was collected by centrifugation and washed several times with deionized water and anhydrous ethanol. A white product was obtained after vacuum drying at 80°C for 12 hours. Finally, 0.1 g of bismuth tungstate was dispersed in 50 mL (1 mg / mL) of NaOH solution, stirred for 1 hour, and washed and dried to obtain oxygen vacancy bismuth tungstate (denoted as O-BWO).
[0038] 2) Dissolve 2.7029 g of ferric chloride hexahydrate and 0.9892 g of manganese chloride tetrahydrate in deionized water and stir for 30 minutes. Then, while stirring for 1 hour, add 10 mL of 0.08 mol / L sodium hydroxide solution dropwise. Place the solution in a 100 mL stainless steel autoclave and heat at 180°C for 10 hours. Finally, cool the solution to room temperature, filter, wash, and dry in an oven at 60°C for 12 hours to obtain manganese ferrite (MFO).
[0039] 3) 0.1 g of bismuth tungstate and 0.008 g of manganese ferrite were mixed and dispersed in 50 mL (1 mg / mL) NaOH solution and stirred for 2 h. The mixture was washed and dried to obtain a manganese ferrite / oxygen vacancy bismuth tungstate composite material (denoted as 20MFO / O-BWO).
[0040] The O-BWO, MFO and 20MFO / O-BWO prepared in step 1), step 2) and step 3) were subjected to XRD test. The test results are as follows: Figure 1 As shown in the figure, it can be seen that the typical characteristic peaks of O-BWO and MFO were detected in 20MFO / O-BWO, indicating the successful preparation of 10MFO / O-BWO.
[0041] The prepared 20MFO / O-BWO was subjected to SEM test. Figure 2 、 Figure 3 and Figure 4 As shown in the figure, MFO has an irregular prismatic structure, O-BWO has a flower-like structure formed by stacking nanosheets, and MFO grows on the surface of O-BWO, indicating the successful synthesis of 20MFO / O-BWO.
[0042] Example 4 Photocatalytic Reduction of Carbon Dioxide Using 20MFO / O-BWO Photocatalyst
[0043] The 20MFO / O-BWO photocatalyst prepared in Example 3 was subjected to a photocatalytic reduction of carbon dioxide experiment. The test process was as follows: using a 300W xenon lamp as the light source, 0.03g of O-BWO, MFO, and 20MFO / O-BWO prepared above were placed in a laboratory-made sealed reaction container with 1mL of deionized water. The sealed container was evacuated with a vacuum pump and carbon dioxide gas was passed through for three cycles, and then carbon dioxide was reduced under visible light irradiation. Figure 5 、 6 As shown in the figure, it can be seen that the manganese ferrite / bismuth tungstate photocatalyst prepared in Example 3 exhibits good photocatalytic activity and stability, and the carbon monoxide generation rate of 20MFO / O-BWO reaches 27.3 μmol h -1 g -1 , while the carbon monoxide generation rate of O-BWO was only 8.8 μmol h -1 g -1 .
[0044] Example 5 A manganese ferrite / bismuth tungstate photocatalyst (the molar ratio of manganese ferrite to the total molar mass of the composite material is 3:10)
[0045] 1) Dissolve 0.33 g of sodium tungstate dihydrate, 0.97 g of bismuth nitrate pentahydrate, and 0.05 g of hexadecyltrimethylammonium bromide in 80 mL of deionized water. The resulting solution was stirred at room temperature for 2 hours, then transferred to a 100 mL stainless steel autoclave and heated at 120°C for 24 hours. The naturally cooled precipitate was collected by centrifugation and washed several times with deionized water and anhydrous ethanol. A white product was obtained after vacuum drying at 80°C for 12 hours. Finally, 0.1 g of bismuth tungstate was dispersed in 50 mL (1 mg / mL) of NaOH solution, stirred for 1 hour, and washed and dried to obtain oxygen vacancy bismuth tungstate (denoted as O-BWO).
[0046] 2) Dissolve 2.7029 g of ferric chloride hexahydrate and 0.9892 g of manganese chloride tetrahydrate in deionized water and stir for 30 minutes. Then, while stirring for 1 hour, add 10 mL of 0.08 mol / L sodium hydroxide solution dropwise. Place the solution in a 100 mL stainless steel autoclave and heat at 180°C for 10 hours. Finally, cool the solution to room temperature, filter, wash, and dry in an oven at 60°C for 12 hours to obtain manganese ferrite (MFO).
[0047] 3) 0.1 g of bismuth tungstate and 0.014 g of manganese ferrite were mixed and dispersed in 50 mL (1 mg / mL) NaOH solution and stirred for 2 h. The mixture was washed and dried to obtain a manganese ferrite / oxygen vacancy bismuth tungstate composite material (denoted as 30MFO / O-BWO).
[0048] The O-BWO, MFO and 30MFO / O-BWO prepared in step 1), step 2) and step 3) were subjected to XRD test. The test results are as follows. Figure 1 As shown in the figure, it can be seen that the typical characteristic peaks of O-BWO and MFO were detected in 30MFO / O-BWO, indicating that 30MFO / O-BWO was successfully prepared.
[0049] Example 6 Photocatalytic Reduction of Carbon Dioxide Using 30MFO / O-BWO Photocatalyst
[0050] The 30MFO / O-BWO photocatalyst prepared in Example 5 was used to perform a photocatalytic reduction of carbon dioxide experiment. The test process was as follows: Using a 300W xenon lamp as the light source, 0.03g of O-BWO, MFO, and 30MFO / O-BWO prepared above were placed in a laboratory-made sealed reaction vessel with 1mL of deionized water. A vacuum pump was used to evacuate the sealed vessel and pass carbon dioxide gas through it for three cycles, and then carbon dioxide was reduced under visible light irradiation. Figure 5 、 6 As shown in the figure, it can be seen that the manganese ferrite / bismuth tungstate photocatalyst prepared in Example 5 exhibits good photocatalytic activity and stability, and the carbon monoxide generation rate of 30MFO / O-BWO reaches 21.6 μmol h -1 g -1 , while the carbon monoxide generation rate of O-BWO was only 8.8 μmol h -1 g -1 .
[0051] Example 7 A manganese ferrite / bismuth tungstate photocatalyst (the molar ratio of manganese ferrite to the total molar mass of the composite material is 5:10)
[0052] 1) Dissolve 0.33 g of sodium tungstate dihydrate, 0.97 g of bismuth nitrate pentahydrate, and 0.05 g of hexadecyltrimethylammonium bromide in 80 mL of deionized water. The resulting solution was stirred at room temperature for 2 hours, then transferred to a 100 mL stainless steel autoclave and heated at 120°C for 24 hours. The naturally cooled precipitate was collected by centrifugation and washed several times with deionized water and anhydrous ethanol. A white product was obtained after vacuum drying at 80°C for 12 hours. Finally, 0.1 g of bismuth tungstate was dispersed in 50 mL (1 mg / mL) of NaOH solution, stirred for 1 hour, and washed and dried to obtain oxygen vacancy bismuth tungstate (denoted as O-BWO).
[0053] 2) Dissolve 2.7029 g of ferric chloride hexahydrate and 0.9892 g of manganese chloride tetrahydrate in deionized water and stir for 30 minutes. Then, while stirring for 1 hour, add 10 mL of 0.08 mol / L sodium hydroxide solution dropwise. Place the solution in a 100 mL stainless steel autoclave and heat at 180°C for 10 hours. Finally, cool the solution to room temperature, filter, wash, and dry in an oven at 60°C for 12 hours to obtain manganese ferrite (MFO).
[0054] 3) 0.1 g of bismuth tungstate and 0.0323 g of manganese ferrite were mixed and dispersed in 50 mL (1 mg / mL) NaOH solution and stirred for 2 h. The mixture was washed and dried to obtain a manganese ferrite / oxygen vacancy bismuth tungstate composite material (denoted as 50MFO / O-BWO).
[0055] The O-BWO, MFO and 50MFO / O-BWO prepared in step 1), step 2) and step 3) were subjected to XRD test. The test results are as follows. Figure 1 As shown in the figure, it can be seen that the typical characteristic peaks of O-BWO and MFO were detected in 50MFO / O-BWO, indicating that 50MFO / O-BWO was successfully prepared.
[0056] Example 8 Photocatalytic Reduction of Carbon Dioxide Using 50MFO / O-BWO Photocatalyst
[0057] The 50MFO / O-BWO photocatalyst prepared in Example 7 was used to conduct a photocatalytic reduction of carbon dioxide experiment. The test process was as follows: Using a 300W xenon lamp as the light source, 0.03g of O-BWO, MFO, and 50MFO / O-BWO prepared above were placed in a laboratory-made sealed reaction container along with 1ml of deionized water. The sealed container was evacuated with a vacuum pump and then passed through with carbon dioxide gas for three cycles. The carbon dioxide was then reduced under visible light irradiation. Figure 5 、 6 As shown in the figure, it can be seen that the manganese ferrite / bismuth tungstate photocatalyst prepared in Example 7 exhibits good photocatalytic activity and stability, and the carbon monoxide generation rate of 50MFO / O-BWO reaches 19.1 μmol h -1 g -1 , while the carbon monoxide generation rate of O-BWO was only 8.8 μmol h -1 g -1 .
Claims
1. A manganese ferrite / bismuth tungstate heterojunction photocatalyst, characterized in that: The molar ratio of the manganese ferrite to the total molar mass of the heterojunction photocatalyst is 1:10, 2:10, 3:10 or 5:
10.
2. The method for preparing a manganese ferrite / bismuth tungstate heterojunction photocatalyst according to claim 1, characterized in that: The steps include: 1) Dissolve sodium tungstate dihydrate, bismuth nitrate pentahydrate and hexadecyltrimethylammonium bromide in deionized water and perform hydrothermal reaction to obtain bismuth tungstate; 2) dissolving ferric chloride hexahydrate and manganese chloride tetrahydrate in water, adding sodium hydroxide solution, and subjecting to a hydrothermal reaction to obtain manganese ferrite; 3) dissolving bismuth tungstate and manganese ferrite in a sodium hydroxide solution, stirring, and drying to obtain a manganese ferrite / bismuth tungstate heterojunction photocatalyst.
3. The preparation method according to claim 2, characterized in that In step 1), sodium tungstate dihydrate: bismuth nitrate pentahydrate = 0.1-1 g: 0.5-1.5 g.
4. The preparation method according to claim 2, characterized in that In step 1), the amount of cetyltrimethylammonium bromide added is 0.05-1 g.
5. The preparation method according to claim 2, characterized in that In step 1), the temperature of the hydrothermal reaction is 80-150° C., and the time of the hydrothermal reaction is 18-36 hours.
6. The preparation method according to claim 2, characterized in that In step 2), ferric chloride hexahydrate: manganese chloride tetrahydrate: sodium hydroxide = 1-4 g: 0.5-1.5 g: 0.0008-0.001 mol.
7. The preparation method according to claim 2, characterized in that In step 2), the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 6-18 hours.
8. The preparation method according to claim 2, characterized in that In step 3), the stirring time is 1-5h.
9. Use of the manganese ferrite / bismuth tungstate heterojunction photocatalyst according to claim 1 in photocatalytic reduction of carbon dioxide.
10. The use according to claim 9, characterized in that The method is as follows: under visible light irradiation, a manganese ferrite / bismuth tungstate heterojunction photocatalyst is placed in a closed space filled with carbon dioxide gas to reduce the carbon dioxide gas to carbon monoxide gas.
Citation Information
Patent Citations
Graphene based bismuth tungstate composite photocatalyst, preparation method and application thereof
CN105363433A
Preparation method, product and application of tungsten oxide / titanium dioxide heterojunction composite visible photocatalyst
CN107715864A
Preparation method of bismuth tungstate visible-light-driven photocatalyst and application of bismuth tungstate visible-light-driven photocatalyst
CN110550661A
Bismuth tungstate composite photo-catalyst with bismuth and oxygen vacancies as well as preparation method and application thereof
CN112156770A
BiFeO3 / Bi2WO6 two-dimensional single-crystal heterojunction photocatalyst as well as preparation method and application thereof
CN116273039A
Cited By
Manganese ferrite / zinc gallate heterojunction photocatalyst as well as preparation method and application thereof
CN121972184A
Manganese ferrite / silver hexabromo-cesium bismuthate heterojunction photocatalyst as well as preparation method and application thereof
CN122424840A